(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2025)
Introduction: Patients with hemophilia often experience joint bleeding that causes pain and atrophy usually in the knees, elbows and ankles. This negatively affects their healthrelated quality of life (HRQoL). There are no previous studies that evaluate coping strategies with chronic pain and HRQoL in these patients by implementing diaphragmatic breathing (DB). Objective: To evaluate the effect of a psychological intervention to improve HRQOL, coping strategies for chronic pain, and stress management in patients with Hemophilia using DB. Method: Single-case quasi-experimental design study (pretest/posttest), with convenience sampling. A 26-year-old man with severe type A Hemophilia participated. The Hemophilia-Specific Quality of Life, Coping with Chronic Pain, Perceived Stress and the Chronic Pain Grading Scale questionnaires were used. DB exercises were applied. The Wilcoxon test was used. Results: The levels of quality of life, gradation of chronic pain and stress decreased, while the levels of coping with chronic pain increased. Significant favorable effects were found with the psychological intervention using DB exercises.Conclusion: DB exercises are non-invasive techniques that may improve the HRQL of people with Hemophilia. This could be an alternative to reduce the characteristic symptoms of the disease.